A Retrospective Analysis of the Relationship of Non-communicable Diseases - Chumpong, Supichaya; Chumpong, Kittisak (Princess of Naradhiwas University Journal, 2023)
This research aimed to study the association rules as the probability of developing noncommunicable diseases when other noncommunicable diseases had previously occurred. The participants were 18,203 from Pakphanang Hospital, Pakphanang, Nakhon Si Thammarat. The investigation used data mining as an association rule technique to identify the relationship of noncommunicable diseases. The results showed that the patients between the ages of 45 and 64 with diabetes, obesity and dyslipidemia have approximately 93.0% hypertension while the patients over the ages of 60 with chronic kidney disease and dyslipidemia have approximately 92.1% hypertension. Moreover, hypertension, diabetes and dyslipidemia are interrelated which can compare the risk of occurring as well.